Studi Eksperimen Gorga Mandailing Siswa Kelas VII SMP Swasta Nurul Ilmi Ditinjau Dari Prinsip-Prinsip Ragam Hias - Kofifah Indar Prawansyah; Sugito Sugito (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This research aims to analyze the application of decorative principles in drawing the Mandailing gorga by class VII students at Nurul Ilmi Private Middle School. This research uses a qualitative descriptive method with data collection techniques form of experimentation, observation and documentation. The research results show that students understanding of the principles decoration, such as composition, motifs, stylization and media is still relatively low. This is caused by a lack of time allocated for arts and culture lessons and a lack students understanding of the local gorga Mandailing. The work produced by students does not fully reflect the optimal application of decorative principles, both from a technical and aesthetic perspective. This research concludes that learning fine arts based on local wisdom requires a more focused approach, adequate time, and more innovative methods to increase students' understanding and creativity in creating art.